An analysis of Al-Kindi and John of Damascus’s argument and allegation of the inconcistencies in the Qur’an - Muhammad Arif Musa; Ahmad Sanusi Azmi; Adnan Mohamed Yusoff (University of Malaya, 2024)
Indexed by WOS/Scopus/MyCite